2007
DOI: 10.1183/09031936.00147706
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms and Ca2+handling in airway smooth muscle

Abstract: Asthma is a disease characterised by reversible contraction of airway smooth muscle. Many signalling pathways are now known to underlie that contraction, almost all of which revolve around Ca 2+ handling. Ca 2+ homeostasis in turn is governed by a wide variety of ionic mechanisms, which are still poorly understood. The present review will briefly summarise those mechanisms that have been recognised for decades, but will then devote considerable attention to several novel ionic signalling mechanisms such as cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 191 publications
(230 reference statements)
4
69
2
Order By: Relevance
“…Apparently, the inhibited activity of NSCCs can be explained by a reduction in the functional TRPC3-encoded channels. The resting Vm normally is between -40 and -50 mV in ASMCs, which is to a great extent less negative than the K 1 equilibrium potential of approximately 285 mV (11,12). It has been shown that native NSCCs are associated with the less negative resting Vm in rabbit pulmonary and coronary artery SMCs (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the inhibited activity of NSCCs can be explained by a reduction in the functional TRPC3-encoded channels. The resting Vm normally is between -40 and -50 mV in ASMCs, which is to a great extent less negative than the K 1 equilibrium potential of approximately 285 mV (11,12). It has been shown that native NSCCs are associated with the less negative resting Vm in rabbit pulmonary and coronary artery SMCs (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms are being investigated, membrane depolarization has been found in ovalbumin-sensitized/challenged ASMCs (11,12). Presumably, membrane depolarization may increase the cell excitability and sensitivity to contractile agonists or can cause extracellular Ca 21 influx, contributing to airway muscle hyperresponsiveness.…”
mentioning
confidence: 99%
“…There is evidence that plasma membrane Ca 2ϩ dependent Cl Ϫ channels are activated in ASM after procontractile stimuli and can allow for the egress of chloride out of the cell (12,40), which not only promotes plasma membrane depolarization, but may also provide a favorable gradient for subsequent sarcolemmal Ca 2ϩ handling during procontractile stimuli (9). Recent evidence Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Important advances have been made in the current understanding of the mechanisms underlying these Ca 2+ oscillations. These have been described in far greater detail than is possible here [36,37,40,41], and the biophysical and pharmacological properties of the cellular machines (pumps and channels) involved in triggering and propagating these Ca 2+ waves have been reviewed elsewhere [42,43]. The present study simply introduces the various cellular entities which are involved.…”
Section: Where Do We Go Next?mentioning
confidence: 99%